An Impactful University Based on Islamic Values (A Case Study of the Synergy between UIN Walisongo and BUMDes Lumintu) / Kampus Berdampak Berbasis Nilai Islam (Studi Kasus Sinergi UIN Walisongo dan BUMDes Lumintu) - Alifa Nur Fitri; Amelia Rahmi; Mustofa Hilmi (Alhadharah: Jurnal Ilmu Dakwah, 2025)
The government initiated an impactful campus program, namely the role of campuses that not only produce graduates but also transform people's lives. One of them is through campus social responsibility based on Islamic values. This study aims to explore the contribution of universities in developing networks and digitizing BUMDes Lumintu in Blora Regency and at the same time carry out the role of preaching in society through Islamic values. This study uses a qualitative descriptive method with data collection techniques through observation and in-depth interviews with BUMDes managers, lecturers, students, and other stakeholders. Data were analyzed systematically to understand the role of campuses in village empowerment. The results of the study show that universities play an important role in strengthening networks through collaboration with the government and community. Despite challenges in infrastructure and community involvement, the synergy between academics, government, and the community in different ways, namely through taujih, irsyad and himayah has proven effective in supporting BUMDes development. The University Social Responsibility (USR) approach provides a relevant model for village empowerment, emphasizing the importance of active participation from all parties. Sustainable and collaborative programs are expected to be a catalyst for more independent and sustainable village development.